ISO 14001 environmental systems handbook - Whitelaw, Ken. (Elsevier/Butterworth-Heinemann, 2004)
ISO 14001 Environmental Systems Handbook Second Edition outlines the scope and purpose of the standard, making it accessible to all. The author begins by explaining the concepts of the standard, which sets the tone for a practical guide to implementation of an ISO 14000-compliant environmental management system, which also covers the consultant's and auditor's perspective. The case studies from industries that have actually undergone the process have been updated to include information on their progress toward environmental objectives in the 18-24 months following implementation. A new case stu.